DETERMINATION OF SEISMIC VULNERABILITY INDEX AND SEDIMENT THICKNESS USING THE HVSR METHOD IN PALU CITY AREA - Marwah S; Rusydi M; Kurniawan M; Rustan Efendi; Rusli M; Sesa E (Tadulako Science and Technology Journal, 2023)
The Palu City area is one of the areas that are vulnerable to the impact of the earthquake, seen from the seismicity and the Palu-Koro fault. Therefore, it is necessary to analyze the seismic vulnerability index and the thickness of the sediment layer in the Palu city area. This study uses the microtremor method with HVSR (Horizontal to Vertical Spectrum Ratio) analysis. The HVSR method produces natural frequency parameters (fo) and amplification (Ao) which are presented in the form of an H/V curve so that this method can estimate the seismic vulnerability index (Kg). The H/V then becomes the input for the ellipticity curve analysis to get the thickness of the sediment layer (h). The results of the study show that the Kg value ranges from 0.16 to 37.09. The lowest Kg value is located at the point MP2234-14 (Kawatuna Village). ) and the highest Kg value is located at MP2234-06 (Petobo Village), the high Kg value tends to be in the valley area and areas close to the coast, while the hillside tends to be low. The results of the analysis of the thickness of the sediment layer (h) ranged from 7 m to 128 m, the thick sediment layer is in the valley and coastal areas, while the thin sediment layer tends to be in the area oh the hills